Residence time distribution of powders in a vertical single screw reactor: experiments using salt-coated tracer particles and simulations - Rajendra, R. Sriram; Palgadhmal, Anil V.; Kulkarni, Amol A. (Particuology, 2025)
The use of single and twin-screw extruders for solid-phase reactions is a promising method to intensify a process in a more sustainable manner. In this manuscript, we report a detailed analysis of the residence time distribution (RTD) in vertical single-screw reactors. The results will help in the selection of the right screw design that would help achieve the desired residence time, which is necessary for a reaction to happen. Experiments were conducted in three vertical screw reactors (having fixed shaft diameter) with varying dimensions using granular free-flowing powders of sodium chloride and silica with a mean particle size of similar to 25 mu m. RTD behavior was modeled using the radial particle velocities in the screw reactor's centrifugal field. Further, a method is proposed for estimating the axial dispersion coefficient of dry powders in such sheared flows using true and bulk densities of the powder and the screw shear rate. This dispersion coefficient is used in the axially dispersed plug flow model to describe the RTD behavior of screw reactors with acceptable accuracy. The theoretically predicted and experimentally obtained dispersion coefficients are found to be similar thereby confirming the suitability of the model. (c) 2025 Chinese Society of Particuology and Institute of Process Engineering, Chinese Academy of Sciences. Published by Elsevier B.V. All rights are reserved, including those for text and data mining, AI training, and similar technologies.
Keywords: Bulk density; Centrifugal field in screw reactor; Particle inertial number; Powder dispersion coefficient; Powder flow; Single-screw extruder